Use of (Z)-β-(2-Fluorobenzenesulfonyl)vinylamines as Novel Synthons in the Synthesis of 1,4-Benzothiazine Derivatives - Tsui, Gavin Chit; Singjunla, Yuttapong; Lautens, Mark (Synthesis, 2012)
A novel synthetic route for arylated 1,4-benzothiazine derivatives has been developed. This method utilizes a key intramolecular nucleophilic aromatic substitution step of the corresponding (Z)-β-(2-fluorobenzenesulfonyl)vinylamine intermediate to construct the benzothiazine ring. A wide range of aryl and heteroaryl substituent groups can be installed from commercial boronic acids. Both mono- and diarylated products have been synthesized in good yields and with good functional group tolerance.
Keywords: heterocycles; rhodium; sulfone; nucleophilic aromatic substitution; cyclization